Developing criteria and design transformation process in designing landscape elements based on nature and Islamic principles - Muslim, Zulkifli (2014)
Elements and materials used in designing urban landscape should reflect the identity of places, particularly the historical sites. There is a lack of consideration in integrating the cultural and environmental resources such as local plants to contribute to the material and design production of local urban spaces. There is a need for a clear understanding on the source of an idea, design process, development and design system. This paper examines the potential of systematic design process in producing designed elements based on the nature and cultural principles, shapes and forms. It looks into the symbiotic relationship between local plants (flower) and the Islamic concept as principles in designing various elements in the built environment and natural setting. The design experiment adopted the researcher's framework of design transformation process first identifies the criteria for the transformation process and then experimenting the manipulation of forms and shapes using the local plants as the source of ideas. Feedback from 159 students with design background from four local universities was gathered through questionnaire survey to identify the functions of the design transformation process and its effectiveness in the producing design variations in shapes and forms of tile design based on plants images. The experiment on tiles design shows that in designing the elements, the importance of the transformation process is emphasized through a systematic transformation process. Supporting the finding, results from the questionnaire survey indicated the importance of systematic design processes in producing variation in the design. These findings will support a more creative system in making urban landscape elements such as floor tiles and l posts that display a unique identity to a place and suit the local environment and culture.